ABOUT THE EDUCATIONAL IMPACT OF STUDENT YOUTH MARITAL STUDENTS - Bakhtiyor Choriyevich, Berdiyev (European Journal of Life Safety and Stability (2660-9630), 2021)
This article discusses the issues of attracting students to physical education and sports, as well as to martial arts. Based on the analysis data presented in the scientific and methodological literature, the author studied a number of modern ways to improve the process of self-education through martial arts classes among students. A wide range of types of combat sports in higher educational institutions contributes to the development of students’ self-discipline and self-education leads to the development of physical, psychological, moral and intellectual qualities.